Current status of aquaculture in the world: COVID-19 first impacts (Research, Society and Development, 2020)
The objective of this work is to understand the current scenario, based on the general analysis of aquaculture and some facts related to this activity, highlighting the first signs of aquaculture in response to a pandemic, in addition to prospecting trends in how the association will be affected after a COVID-19 pandemic. The study is exploratory in nature using the bibliographic research method, where the survey takes place from January to June 2020, through the consultation of official platforms, however, this scenario had to be changed, due to interruptions in the daily activities of the entire population, especially social isolation, border restrictions and reduction of air travel in several countries in an attempt to increase the spread of the disease. This scenario created challenges for the commercialization of fish, which may be reflected in long-term impacts on the chain.